A simplification of reading thermodynamic properties using microsoft excel - Nur Diyana Wahida, Adam (2012)
Thermodynamic properties calculator is an engineering tool built by MS Excel addin which is properties of water, air and superheated vapor. The main purpose of this project is to excel file that can simply obtain thermodynamic properties without manually reading from thermodynamic properties table. The project scopes werefluids that will be used as a reference were water, superheated vapor and air, thermodynamic properties such as enthalpy, entropy, specific heat, thermal conductivity, specific volume, relative pressure ratio, specific volume ratio and internal energy were the main properties that need to be referred. All the properties were based on thermodynamic properties table and result validation. Formulas that suitable to the formula of interface created using excel file were identified and studied.All unknown for the common formula that used to do interpolation manually were listed out and identified its function. Then, formula for each unknown created using excel formula and lastly all the formulas created for each unknown were combined according to the common formula used for manual interpolation. The new formula created using excel formulas was tested and evaluated. The value of properties from the interface created was compared to the value of properties from manual interpolation using calculator in order to check the validation of the data. In the nutshell, interface of a simplest way to read thermodynamics properties table using excel software was successfully created and was checked by data validation. In order to improve this project, the function of changing the units of thermodynamics properties to other standard, for example into American Standard, should be developed and the software should also be able to run on other operating systems such as MAC for Apple and LINUX for Linus Torvalds so that people using other operating systems will have the benefits of using the software.